General conditions of application and reasons for release for the liability for the harm caused during self-defense - Ляшевська, Л. І. (Problems of legality, 2014)
The article deals with general conditions of application and reasons for release for the liability for the harm caused during self-defense. The main scientific discussions as for the conditions of liability for the harm caused by a person including self-defense are studied.